Central banking in the Caribbean in the 21st century macroeconomic policy and financial sector stability : how the IMF is helping to strengthen financial systems - Evans, Huw ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Explains what the IMF is doing to try to reduce the frequency and severity of financial crises. focuses on the idea of financial stability.